A systematic review and meta-analysis of the prevalence of norovirus in cases of gastroenteritis in developing countries. Issue 40 (October 2017) - Nguyen, Gia Thanh; Phan, Kevin; Teng, Ian; Pu, Jian; Watanabe, Toru
Abstract: Background: While norovirus (NoV) is well known as a leading causal pathogen for acute gastroenteritis in developed countries, structured data on prevalence in developing countries are not available thus far. This review aims to estimate the prevalence of NoV in cases of gastroenteritis in developing countries based on recently published reports. Methods: Relevant studies were identified by searching PubMed and Web of Science for the period January 1, 1990 through March 31, 2016. We included studies performed in developing countries with a study period of at least 12 months and which provided information on polymerase chain reaction (PCR)-confirmed NoV prevalence in patients diagnosed with acute gastroenteritis. A metaanalysis was conducted on NoV prevalence, focused on viral genogroups GI and GII, in cases of acute gastroenteritis. Results: Using evidence from 178 articles, the estimated NoV prevalence among 148, 867 patients with acute gastroenteritis was 17% (95% confidence interval [CI]: 15–18%). The prevalence decreased from 18% (95% CI: 16–20%) for upper middle-income countries to 15% (13–18%) and 6% (3–10%) for lower middle- and low-income countries, respectively. There were no significant differences in NoV prevalence by age group (under 5 years, 5 years and over, and mixed ages) or severity of symptoms as defined by community, outpatient, or inpatient setting. The pooled prevalence of NoV GII (15%, 95% CI: 13–17%) was significantly higher than that of NoV GI (1%, 95% CI: 1–1%) in patients with acute gastroenteritis. Conclusion: From the evidence considered in this review, the estimated prevalence of NoV in patients with acute gastroenteritis in developing countries was 17%. This estimate can be used to evaluate the burden of NoV-associated acute gastroenteritis in developing countries, which is currently unclear due to poor diagnosis and surveillance systems, and the estimation may enhance the development of human NoV vaccines. Abstract : Supplemental Digital Content is available in the text